Identification of a Receptor-Binding Region within Domain 4 of the Protective Antigen Component of Anthrax Toxin - Varughese, Mini (American Society for Microbiology, 1999)
Anthrax toxin from Bacillus anthracis is a three-component toxin consisting of lethal factor (LF), edema factor (EF), and protective antigen (PA). LF and EF are the catalytic components of the toxin, whereas PA is the receptor-binding component. To identify residues of PA that are involved in interaction with the cellular receptor, two solvent-exposed loops of domain 4 of PA (amino acids [aa] 679 to 693 and 704 to 723) were mutagenized, and the altered proteins purified and tested for toxicity in the presence of LF. In addition to the intended substitutions, novel mutations were introduced by errors that occurred during PCR. Substitutions within the large loop (aa 704 to 723) had no effect on PA activity. A mutated protein, LST-35, with three substitutions in the small loop (aa 679 to 693), bound weakly to the receptor and was nontoxic. A mutated protein, LST-8, with changes in three separate regions did not bind to receptor and was nontoxic. Toxicity was greatly decreased by truncation of the C-terminal 3 to 5 aa, but not by their substitution with nonnative residues or the extension of the terminus with nonnative sequences. Comparison of the 28 mutant proteins described here showed that the large loop (aa 704 to 722) is not involved in receptor binding, whereas residues in and near the small loop (aa 679 to 693) play an important role in receptor interaction. Other regions of domain 4, in particular residues at the extreme C terminus, appear to play a role in stabilizing a conformation needed for receptor-binding activity.